Pengaruh Leader Member Exchange (LMX) dan Quality Work of Life (QWL) terhadap Organizational Citizenship Behavior (OCB) Dosen Sekolah Tinggi Agama Islam Nahdatul Ulama (STAI NU) Jakarta - Indah Mayasari (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2019)
The objective of the research is to obtain information about the effect of leader member exchangeand quality work of life on organizational citizenship behavior on lecture of Islamic College ofNahdatulUlamaof Jakarta (STAI NU). The research was conducted to all of lecture of Islamic college of NahdatulUlama (STAINU) at The City of Jakarta by using a survey method with path analysis applied in testing hypothesis. The number 52 lectures as sample was selected by using Slovin formula. The research conclude: (1) there is direct effect of leader member exchange on organizational citizenship behaviour; (2) there is direct effect of quality work of life on organizational citizenship behaviour; (3). there is direct effect of leader member exchange on quality work of life. Therefore to enhance lecture’s organizational citizenship behaviour can be carried out by leader member exchange, and quality work of life.